Coronary artery disease ameliorates extracellular vesicle lncRNA PUNISHER regulates angiogenic response andendothelial cells function via NFkB-dependent mechanism. (14th October 2021) - Hosen, M R; Nickenig, G; Jansen, F
Abstract: : Augmenting evidence indicates that long noncoding RNAs (lncRNAs) are playing a crucial role in diverse cellular/pathological processes. Intercellular transfer of extracellular vesicles (EVs) transmitted lncRNA regulates vascular health and diseases. However, whether lncRNA expression in EVs is regulated in patients with coronary artery disease, is unknown. A PCR-based lncRNA array analysis revealed that EV-PUNISHER was significantly upregulated in patients with CAD (n=221) compared to healthy subjects. Our data showed that PUNISHER is the most upregulated lncRNA in CAD in accordance with other highly expressed lncRNAs. To examine the specific role of PUNISHER in EC phenotypic regulation, siRNA-mediated silencing in ECs revealed that depletion of PUNISHER suppresses the migration and proliferation of ECs. Moreover, depletion of PUNISHER decreases cell survival by reducing cell viability and proliferation through increased apoptosis and cytotoxicity. In order to investigate EC function in PUNISHER depleted cells, in vitro sprouting and tube formation assay revealed that PUNISHER is an important mediator EC functions, which acts as an anti-angiogenic factor. In vitro atherosclerotic stimuli increased PUNISHER expression in EV/EC in a dose-dependent way. Microarray analysis identified a series of pro- and anti-angiogenic genes as well genes directly involved in cell viability that are differentially regulated. We confirmed that PUNISHER is incorporated into endothelial microvesicles (EMVs) and transferred to recipient cells by using different experiments. By using lncRNA-FISH and vesicle degradation assays, we showed that PUNISHER is incorporated into EMVs, augmented recipient EC function in vitro upon transfer via EMVs. To examine whether EMV-PUNISHER promotes the EC function, different in vitro functional experiments with ECs confirmed that PUNISHER is an important regulator. Mass spectrometry analysis has revealed EMV contains numerous proteins, including RNA binding proteins such as hnRNPU. By using RNA-pulldown and RNA-IP, we confirmed that PUNISHER interacts with hnRNPU, which facilitates packaging into EMV prior to transfer to recipient EC. The interaction acts as an important positive regulator of cell viability and survival of recipient cells, identified using functional assay. Transcription factor array has shown that PUNISHER regulates NFkB to control cellular viability and apoptosis. A murine re-endothelialization model after injection of 1×10 7 EVs or bulk ncRNAs revealed that EV-PUNISHER promotes reendothelialization. Ex vivo internalization/uptake of PKH-67-labeled EVs revealed that EVs are detectable in the cross-section of EV-perfused carotid artery. Our study unveiled for the first time that EV-PUNISHER exerts its function in endothelial cells which might be beneficial in cardiovascular pathologies where the endothelial function is dysregulated. Our data indicate that PUNISHER can be targeted to develop targeted therapeutics. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): German Research Foundation (DFG); German Society of Cardiology (DGK)